Psicologia da pobreza e pobreza da psicologia: um estudo sobre o trabalho de psicólogas(os) na política pública de assistência social - Lima, Vinicius Cesca de (2014)
This study analizes some connections between psychologist profession, social assistance policy (and, within this, specifically poverty combat) and the economical development pattern, from two questions: [1] how is produced the subjective dimension of this professional field and how this dimension determines it or, in other words, how are produced the repertories of meanings which guides, justifies and legitimizes it; [2] how these practices can concretely contribute towards the intended changes. For this, the study is based on three complementary analytical efforts. Firstly, in order to apprehend the relationship between causality and teleology in praxis, we discuss, on historical-dialectical materialism, the ontological foundation of social being. Secondly, we discuss the social and historical bases of poverty in capitalist mode of production, analyzing how poverty became politically represented as a public issue to be addressed by social policies and how these are tensioned contemporarily by the structural crisis of capital. Special attention was given to define these issues in Brazilian contemporary reality, relating social policies to "neodevelopmentalist" economy. It's also discussed the conceptions of poverty and its combat as ideological productions in subjective dimension of reality. Thirdly, we analyze the professional practices of psychologists in this institutional context, based on research involving participative observation in a Reference Center for Social Assistance and analysis of multiple documentary sources. The study revealed some of many theorical and practical challenges for psychologists in social assistance, specially the need to overcome subjectivism and politicism in professional concepts and practices that assume a professional project that aims political emancipation, but is often limited to a more abstract "subjective emancipation", reducing itself, in worst case, to adaptationist reproduction of everyday or, at the best of them, to tragic expression of an ethical intentionality with no material condictions to accomplish